Progesterone for the prevention of threatened miscarriage. Issue 3 (March 2022) - Devall, Adam J.; Melo, Pedro; Coomarasamy, Arri
Abstract: Miscarriage, defined as the loss of a pregnancy before 24 weeks of gestation, is the most common complication of early pregnancy, affecting approximately 15% of clinically recognized pregnancies. The steroid hormone progesterone is essential for the maintenance of pregnancy, and progesterone deficiency is associated with miscarriage. Two important clinical risk factors for miscarriage are a history of previous miscarriages and vaginal bleeding in early pregnancy. Progesterone supplementation has therefore been attempted to prevent miscarriages in asymptomatic women with a history of miscarriages and in women who have started to bleed in early pregnancy. The latest evidence from high quality clinical trial research has shown that vaginal micronized progesterone treatment of women with the dual risk factors of early pregnancy bleeding and a history of one or more previous miscarriages increases the likelihood of a successful live birth (relative rate 1.08, 95% CI 1.02 to 1.15, high-certainty evidence). This treatment has also been shown to be cost-effective, leading to the National Institute for Health and Care Excellence committee for the guideline 'Ectopic pregnancy and miscarriage: diagnosis and initial management (NG126)' updating their guidance to recommend the use of vaginal micronized progesterone to treat women with the dual risk factors of a history of one or more previous miscarriages and early pregnancy bleeding. This change in practice has the potential to prevent up to 8, 450 miscarriages a year in the UK.